Leveraging GenAI for technology foresight - Ellermann, Kai; Seidenberg, Tobias; Asmar, Laban; Knepler, Jonas; Dumitrescu, Roman (Proceedings of the Design Society)
ABSTRACT: Facing increasingly dynamic market environments and global challenges such as climate change and resource scarcity, companies are under constant pressure to innovate and remain competitive. As technology is a key enabler, companies need to understand the drivers of technological change. Technology Foresight systematically identifies and analyzes emerging technologies to support engineering design decisions. However, the growing volume of data is outpacing manual processing capabilities. This research explores the integration of Generative AI to enhance Technology Foresight by automating technology analysis and information synthesis. This paper presents a comprehensive problem analysis, reviews existing solutions, and proposes a framework that demonstrates the potential of Large Language Models combined with a Retrieval Augmented Generation architecture to transform Technology Foresight.

Real-time object detection and localization for airport aprons - Wani, Bhavesh; Yee, Jingye; Eckertz, Daniel; Seidenberg, Tobias; Dumitrescu, Roman (Seventeenth International Conference on Digital Image Processing (ICDIP 2025))

Enabling Better Systems Through Better Teams: 27 Role Profiles for Engineering Advanced Systems - Grote, Eva-Maria; Koldewey, Christian; Schwarz, Stefan Eric; Dumitrescu, Roman; Albers, Albert (2025 IEEE International Conference on Engineering, Technology, and Innovation (ICE/ITMC))

Digital Transformation of Organizational Entities - Fichtler, Timm; Petzke, Lisa Irene; Grigoryan, Khoren; Dumitrescu, Roman; Koldewey, Christian (2025 IEEE International Conference on Engineering, Technology, and Innovation (ICE/ITMC))

Mit digitalen Hebeln zur Kreislaufwirtschaft: Mit digitalen Hebeln zur Kreislaufwirtschaft - Rasor, Anja; Koldewey, Christian; Dumitrescu, Roman (Nachhaltige Industrie)

Prompt Engineering im Systems Engineering - Hovemann, Aschot; Bita, Isaac Mpidi; Aldade, Abed Alrahman; von Heißen, Oliver; Dumitrescu, Roman (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Abstract Große Sprachmodelle wie GPT-4 bieten erhebliche Potenziale für das Systems Engineering. Prompt-Engineering ermöglicht einen flexiblen Einsatz im Anforderungsmanagement, Systementwurf und in der Integration, Verifikation und Validierung ohne aufwendiges Modelltraining. Die Formulierung von Prompts und die Anwendung fortschrittlicher Techniken erfordern jedoch tiefes Domänenwissen. Der Beitrag zeigt Potenziale und Herausforderungen dieser Technik auf und illustriert praktische Anwendungsbeispiele

Advanced Analytics Capability Map for Smart Factories: Supporting the Planning, Design, Management and Operations of Advanced Analytics Use Cases - Weller, Julian; Lick, Jonas; Brock, Jonathan; Heuwinkel, Tim; Hartmann, Stefan; Kühn, Arno; von Enzberg, Sebastian; Dumitrescu, Roman (Procedia CIRP)

Product Management: Tasks, Roles, and the Importance of Data - Grigoryan, Khoren; Martin, Lucas; Lamarz, Jessica; Fichtler, Timm; Hohn, Bennett; Asmar, Laban; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Untangling circular value networks - mechanisms, advantages, risks, and future research - Petzke, Lisa Irene; Rasor, Anja; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)

A serious game to introduce Systems Engineering in interdisciplinary teams - Könemann, Ulf; Niemeyer, Marcel; Schierbaum, Anja; Dumitrescu, Roman (Procedia CIRP)

Assessing and Communicating Software Security: Enhancing Software Product Health with Architectural Threat Analysis - Strüwer, Jan-Niclas; Trentinaglia, Roman; Wohlers, Benedict; Bodden, Eric; Dumitrescu, Roman (AHFE International)
Assessing and communicating software security has become a crucial concern in the era of digital transformation. As software systems grow more complex and interconnected, it becomes increasingly challenging to effectively evaluate and communicate a product's security status to both technical and non-technical stakeholders. The Software Product Health Assistant (SPHA) is designed to automatically collect and aggregate data from existing expert tools and derive, among other scores, a transparent Security Score. SPHA is designed to present and explain this Security Score to decision-makers to support their responsibilities. In this paper, we demonstrate how to integrate data from SMARAGD (System Modeler for Architectural Risk Assessment and Guidance on Defenses), a safety-informed threat modeling tool, into SPHA to enhance the existing definition of its Security Score. To achieve this, we combine information about known vulnerabilities with architectural and threat data to calculate a realistic risk score for the product in question.

SmartHomeFarming: Trends, Challenges, and Solutions in a Digital and Sustainable Future - Bita, Isaac Mpidi; Hermelingmeier, Dominik; Gröger, Stefan; Hovemann, Aschot; Pfeifer, Stefan; Henke, Christian; Dumitrescu, Roman; Trächtler, Ansgar (Procedia CIRP)

Towards a hybrid theory: Derivation of a view concept between Model-based Systems Engineering and Data Analytics - Tissen, Denis; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)

Maker Systems Engineering Systematic: A Practitioner-Driven Research Agenda - Hermelingmeier, Dominik; Bita, Isaac Mpidi; Menne, Leon; Jobelius, Johannes; Tichonov, Denis; Pfeifer, Stefan; Dumitrescu, Roman (Procedia CIRP)

Success Factors in Product Management and the Role of Data - Fichtler, Timm; Petzke, Lisa Irene; Grigoryan, Khoren; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)

The Nexus Model: Towards a metamodel for data-driven system models - Tissen, Denis; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman (Procedia Computer Science)

Linking Abstract Digital Twin Data to 3D Models: A Configurable Approach for Real-Time Adaptation - Eckertz, Daniel; Sander, Mattes; Masroor, Omar; Dumitrescu, Roman (2025 8th International Conference on Information and Computer Technologies (ICICT))

Advanced Systems Engineering - Auswertung des Gesamtbildes ASE - Aktueller Stand zum Ende von AdWiSE - Dumitrescu, Roman; Albers, Albert; Gausemeier, Jürgen; Riedel, Oliver; Lindow, Kai (Forschungsberichte Pflichtabgabe (BMFTR, BMWE…))

AI-Augmented Model-Based Systems Engineering - Bernijazov, Ruslan; Dumitrescu, Roman; Hanke, Fabian; von Heißen, Oliver; Kaiser, Lydia; Tissen, Denis (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Abstract The increasing complexity of modern technical systems necessitates innovative approaches such as Model-Based Systems Engineering (MBSE). In this context, using Artificial Intelligence (AI) emerges as a key enabler for practical application and efficiency improvement. This article introduces a maturity model for AI-based assistance systems in MBSE. It helps companies assess their current automation level in MBSE activities, providing a foundation for strategic planning of process improvements.

Advanced Analytics in Smart Factories: Towards an actionable Taxonomy for Prescriptive Analytics Use Cases - Weller, Julian; Nalavade, Sumit; Gmelch, Oliver; Migenda, Nico; Heuwinkel, Tim; Dumitrescu, Roman (Procedia CIRP)